Faktor-Faktor Yang Mempengaruhi Tingkat Underpriced Saham Perdana Pada Perusahaan Go Public Yang Terdaftar Di Bursa Efek Indonesia - Yusbardini; Christine (Jurnal Ekonomi, 2010)
Actions by the company in conducting an initial public offering or initial public offering (IPO) is an attempt to obtain new funding sources to finance the company's activities, expansion or other investment activities. Price IPO at the IPO is determined upon agreement between the issuer with an underwriter. But in setting the IPO price and information asymmetry sometimes arise between the interests of both parties. From the side of the underwriters, they have information that is more diverse than the issuer so the underwriter is a big chance. This study aimed to identify factors that predicted the factors influencing the level of underpricing in the IPO pricing at the time of initial public offering (IPO), either partially or in companies that go public in Indonesia Stock Exchange (IDX) during the period 2004-2007. The sample taken is a company listed on the Stock Exchange from 2004-2007 and had underpriced. The number of samples that meets the criteria there are 34 companies. To obtain the information needed to process data collection through the documentation. The hypothesis was tested with a multiple linear regression model. From the results of a study of 34 sample companies, indicating that the four factors above, there is no single factor affecting the level of underpriced IPO firms go public during the period 2004-2007 is partially or simultaneously. Suggested authors for future research should increase research time so that samples taken will be more and add another variable to be tested in the can from the company's prospectus.